2010
DOI: 10.1051/0004-6361/200913332
|View full text |Cite
|
Sign up to set email alerts
|

First spectroscopic analysis of β Scorpii C and β Scorpii E

Abstract: Context. The multiple system β Scorpii consists of five components and two suspected members forming a total of seven stars. In the past, this system acquired much interest because of a series of occultation by the planet Jupiter and one of its satellites (Io). The study of this phenomena allowed us to ascertain the principal components of the system and the possible nature of each component. Aims. By using optical spectroscopy, we derive radial velocities, T eff , log g, abundances L/L , M/M , and R/R for β S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Van Flandern & Espenschied (1975) measured unusual colours for E, from which they suggested that this component could be a double system or a peculiar star. More recently, the subsystem CE was analysed by Catanzaro (2010), who reported component E as a single-lined spectroscopic binary and found its orbital parameters. Furthermore, he carried out an abundance analysis using a high-resolution spectrum (R ≈ 70 000) of the visual subsystem.…”
Section: Wds 16054-1948mentioning
confidence: 99%
“…Van Flandern & Espenschied (1975) measured unusual colours for E, from which they suggested that this component could be a double system or a peculiar star. More recently, the subsystem CE was analysed by Catanzaro (2010), who reported component E as a single-lined spectroscopic binary and found its orbital parameters. Furthermore, he carried out an abundance analysis using a high-resolution spectrum (R ≈ 70 000) of the visual subsystem.…”
Section: Wds 16054-1948mentioning
confidence: 99%